Case Report: Massive Hepatocellular Carcinoma Complete Surgical Resection After Portal Vein Embolization and Multimodality Therapy - Lin, Qianyi; Chen, Dexiong; Li, Kangde; Fan, Xiaomin; Cai, Qi; Lin, Weihong; Qin, Chunhong; He, Tao (Frontiers in Radiology, 2022)
A high proportion of massive patients with hepatocellular carcinoma (HCC) are not amenable for surgical resection at initial diagnosis, owing to insufficient future liver remnant (FLR) or an inadequate surgical margin. For such patients, portal vein embolization (PVE) is an essential approach to allow liver hypertrophy and prepare for subsequent surgery. However, the conversion resection rate of PVE only is unsatisfactory because of tumor progression while awaiting liver hypertrophy. We report here a successfully treated case of primary massive HCC, where surgical resection was completed after PVE and multimodality therapy, comprising hepatic artery infusion chemotherapy (HAIC), Lenvatinib plus Sintilimab. A pathologic complete response was achieved. This case demonstrates for the first time that combined PVE with multimodality therapy appears to be safe and effective for massive, potentially resectable HCC and can produce deep pathological remission in a primary tumor.